RHOQ is induced by DLL4 and regulates angiogenesis by determining the intracellular route of the Notch intracellular domain - Bridges, Esther; Sheldon, Helen; Kleibeuker, Esther; Ramberger, Evelyn; Zois, Christos; Barnard, Alun; Harjes, Ulrike; Li, Ji-Liang; Masiero, Massimo; MacLaren, Robert; Harris, Adrian (Angiogenesis (London), 2020)
Angiogenesis, the formation of new blood vessels by endothelial cells, is a finely tuned process relying on the balance between promoting and repressing signalling pathways. Among these, Notch signalling is critical in ensuring appropriate response of endothelial cells to pro-angiogenic stimuli. However, the downstream targets and pathways effected by Delta-like 4 (DLL4)/Notch signalling and their subsequent contribution to angiogenesis are not fully understood. We found that the Rho GTPase, RHOQ, is induced by DLL4 signalling and that silencing RHOQ results in abnormal sprouting and blood vessel formation both in vitro and in vivo. Loss of RHOQ greatly decreased the level of Notch signalling, conversely overexpression of RHOQ promoted Notch signalling. We describe a new feed-forward mechanism regulating DLL4/Notch signalling, whereby RHOQ is induced by DLL4/Notch and is essential for the NICD nuclear translocation. In the absence of RHOQ, Notch1 becomes targeted for degradation in the autophagy pathway and NICD is sequestered from the nucleus and targeted for degradation in lysosomes.